Finite propagation speed and kernels of strictly elliptic operators - David Gurarie (International Journal of Mathematics and Mathematical Sciences)
We establish estimates of the resolvent and other related kernels and discuss Lp-theory for a class of strictly elliptic operators on Rn. The class of operators considered in the paper is of the form A0+B with the leading elliptic part A0 and a singular perturbation B, whose coefficients have Lp-type and are modeled after Schrödinger operators.